Adverbs of change and dynamicity - Koev, Todor (Natural language and linguistic theory, 2025)
This paper makes two contributions, one empirical and one theoretical. The empirical focus is “adverbs of change”—modifiers such as quickly , slowly , and immediately , which characterize the change described by the modified predicate as fast or slow. Based on quickly as the most versatile exemplar, the paper develops a semantic account that is uniform both across and within such adverbs. Specifically, I argue that adverbs of change share a common semantic core that selects for dynamic predicates and measures out event duration. I further argue that individual adverbs are not lexically ambiguous, despite their ability to take on different readings—namely rate, extent, narrative, or illocutionary. Instead, these different readings arise through interaction with aspectual and discourse structure, and are further restricted by idiosyncratic scope possibilities. The proposed account of adverbs of change has theoretical implications for the aspectual notion of dynamicity, suggesting that dynamicity is built directly into the mereological structure of events. More concretely, dynamic predicates are claimed to refer to “transitions”, a kind of complex event that labels the change that has occurred. Overall, the paper aims to lay the groundwork for a general theory of verbal change that correctly predicts the implication relations between key aspectual features such as dynamicity, telicity, and durativity.